A Natural Transition Between Equilibrium Patterns of Dislocation Dipoles - Zhu, Y; Chapman, S (2014)
The equilibrium configurations of a row of uniformly distributed dislocation dipoles are first studied. The analysis is then generalised to study dipoles in two-dimensional rectangular periodic lattices. By examining the stability of the equilibrium configurations we find that the system may undergo a natural transition from the Taylor lattice to a row of dipole walls. This bifurcation may be involved in the transition from channel-vein to persistent slip band (PSB) structures in the early stage of metal fatigue. © 2014 Springer Science+Business Media Dordrecht.